2007
DOI: 10.1091/mbc.e06-08-0751
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of AtNUC-L1 Reveals a Central Role of Nucleolin in Nucleolus Organization and Silencing of AtNUC-L2 Gene in Arabidopsis

Abstract: Nucleolin is one of the most abundant protein in the nucleolus and is a multifunctional protein involved in different steps of ribosome biogenesis. In contrast to animals and yeast, the genome of the model plant Arabidopsis thaliana encodes two nucleolin-like proteins, AtNUC-L1 and AtNUC-L2. However, only the AtNUC-L1 gene is ubiquitously expressed in normal growth conditions. Disruption of this AtNUC-L1 gene leads to severe plant growth and development defects. AtNUC-L1 is localized in the nucleolus, mainly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
217
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(230 citation statements)
references
References 49 publications
13
217
0
Order By: Relevance
“…2). In spite of the phenotypic similarity of apum23 mutant to the "loss of function" mutants of nucleolin 1 (AtNuc-L1) [46][47][48] and ribosomal protein (RP) [49][50][51][52] genes, our microarray data showed the transcriptional upregulation of a portion of the RP genes, although the expression level of the AtNuc-L1 transcript did not change. However, AtNuc-L2, which is not expressed under normal growth conditions in wild-type plants, was greatly upregulated.…”
Section: Apum23 Is Required For Normal Growth Patterning and Developmmentioning
confidence: 91%
See 1 more Smart Citation
“…2). In spite of the phenotypic similarity of apum23 mutant to the "loss of function" mutants of nucleolin 1 (AtNuc-L1) [46][47][48] and ribosomal protein (RP) [49][50][51][52] genes, our microarray data showed the transcriptional upregulation of a portion of the RP genes, although the expression level of the AtNuc-L1 transcript did not change. However, AtNuc-L2, which is not expressed under normal growth conditions in wild-type plants, was greatly upregulated.…”
Section: Apum23 Is Required For Normal Growth Patterning and Developmmentioning
confidence: 91%
“…AtNuc-L1 is also required in pre-rRNA processing, similar to APUM23. 46,48 Hence, AtNuc-L2 appears to be upregulated to compensate for the reduced supply rate of rRNA. Upregulation of RP gene expression in the apum23 mutant also may be a feed-back mechanism to compensate either the reduced rate of ribosome assembly or the imbalance of ribosome subunits due to a limited supply of integral rRNAs.…”
Section: Apum23 Is Required For Normal Growth Patterning and Developmmentioning
confidence: 99%
“…Since Ki-67 is also dispersed in nucleoli after nucleolin depletion, we hypothesize that the apparent nucleolar dispersions of these three proteins in nucleolin-depleted cells probably arise as a consequence of disorganization of the nucleolar structure. It has been reported that mutations in genes encoding nucleolin homologues in fission yeast (GAR2) and Arabidopsis (AtNUC-L1) have severe effects on the organization of nucleoli (Léger-Silvestre et al, 1997;Pontvianne et al, 2007). However, the function of nucleolin in the organization of nucleoli has not been reported in animal cells.…”
Section: Nucleolin Is Required For Nucleolus Formationmentioning
confidence: 99%
“…A detailed analysis of the 3'ETS sequences revealed the presence of 3 (VAR2), 4 (VAR1 and VAR3) or 5 rDNA chromatin decondensation and affects expression of specific 45S rRNA gene variants. 1,16 Here we present additional characterization of these rDNA gene variants and discuss their possible impact on rDNA chromatin organization and gene expression.…”
Section: Variations On a Teammentioning
confidence: 99%